Characterization of dysbiosis of the conjunctival microbiome and nasal microbiome associated with allergic rhinoconjunctivitis and allergic rhinitis - Wang, Yuan; Li, Xuan; Gu, Shuntong; Fu, Junhong (Frontiers in Immunology, 2023)
Background: Allergic rhinoconjunctivitis (ARC) and allergic rhinitis (AR) are prevalent allergic diseases. People are increasingly aware of the impact of microbial disorders on host immunity and allergic diseases. This study aimed to assess the changes in the conjunctival and nasal microbiome of patients with ARC or AR. Methods: Conjunctival swabs and nasal swabs were collected from every subjects for 16S rRNA amplicon sequencing. The bacterial community profile was analyzed. Results: A total of 40 ARC patients, 20 AR patients, and 34 healthy controls were recruited. To measure differences in taxonomic diversity among the three groups, the Chao1, Observed-otus, Shannon, and Simpson indexes were calculated. The Chao1 index and Observed-otus index of conjunctival microbiome in ARC and AR groups tended to be lower than healthy controls. A lower Shannon index and Simpson index of conjunctival microbiome were found in AR group compared with the other two groups. Both the Shannon index and Simpson index of nasal microbiome in ARC and AR groups tended to be lower than healthy controls. This study found significant differences in the microbiota components of patients with ARC or AR compared to healthy controls. However, there was no significant difference between ARC group and AR group. In addition, the functions of the microbial communities were altered in ARC and AR groups. Conclusions: Our study demonstrates changes in the composition and function of the conjunctival and nasal microbiome in patients with ARC or AR, which suggests that there is a relationship between allergic conditions and local microbiome.